Climate Risk and Bank Capital Structure - Yassine Bakkar (Queen's University Belfast, Queen's Business School, 2023)
We study the role of climate risk exposure in the dynamic behavior of banks' regulatory capital adjustment using a large European sample from 39 countries during the 2006-2021 period. We find that banks facing high exposure to climate risk opt for higher target (regulatory) capital adequacy ratio and make faster adjustment to their optimal capital structure, especially if they are more exposed to carbon pollution. Such banks boost their adjustment during the post Paris Agreement period. These banks move to their target capital adequacy ratio by mainly adjusting their risk-weighted assets or by reallocating them more promptly than other peers, but without necessarily altering assets, particularly, lending. This paper lends support to the importance of the climate change-related risks into prudential supervision to protect the financial system's resilience and contributes to the debate on climate-related capital requirements.
Keywords: G21; G28; Q53; Q54; 330; Dynamic capital structure; Speed of adjustment; Climate change; Paris Agreement; Balance sheet composition